Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Pemahaman Akuntansi dan Bisnis (Studi Empiris Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Solichah, Erina Umahatus; Malikah, Anik; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This think about points to decide the impact of mental insights, passionate insights and otherworldly insights on bookkeeping and commerce understanding. This consider decided financial matters and commerce understudies at the Islamic College of Malang as the consider populace. In the interim, the slovin equation was utilized to choose a test of 68 respondents. This investigate strategy employments quantitative strategies, whereas for data collection procedures employing a survey surveyed with a 5-point Likert Scale. This ponder employments different straight relapse investigation to analyze the information. The comes about gotten in this consider demonstrate that mental insights and enthusiastic insights have no impact on bookkeeping and trade understanding, whereas otherworldly insights has an impact on bookkeeping and trade understanding.Keywords: Emotional Intelligence, Intellectual Intelligence, Spiritual Intelligence and Accounting & Business.